ANALYSIS OF CLINICAL SIGNS OF A PATIENT'S OSTEOARTHROSIS (World Bulletin of Public Health, 2022)
This article describes the clinical characteristics of female and male patients aged 35 to 65 with a diagnosis of osteoarthritis